Isometopus anlasi sp. nov. (Heteroptera: Miridae) from Turkey - Çerçi̇, Bariş; Dursun, Ahmet (Zootaxa, 2017)
A new species of the genus Isometopus, Isometopus anlasi sp. nov. (Heteroptera: Miridae) is described based on both male and female specimens. Habitus of male, female and last instar nymph, and parameres are illustrated. Data on biology and plant associations of the new species are also recorded. Additionally, an updated key for the European and Middle Eastern species of Isometopus is provided.